Comparison of Condylar Guidance in Opening and Protrusion Using Electronic Axiography and CBCT: An Observational Cross-Sectional Study - Łukasz Lassmann; Agata Żółtowska; Monika Teślak-Piesyk; Riaz Yar (Applied Sciences)
This observational cross-sectional study evaluated the differences in condylar guidance angles during mandibular protrusion and mouth opening using digital axiography and CBCT. A total of 30 healthy subjects (60 TMJs) aged 20–24 years were examined. Mandibular movements were recorded using the Modjaw system, and fossa height was assessed from CBCT images. A statistically significant correlation was observed between condylar angles measured during protrusion and opening (r = 0.57, p < 0.001). Protrusive measurements were more consistent, while opening exhibited greater variability. The results suggest that protrusive movements are more reliable for articulator programming. Digital tools such as Modjaw can enhance precision and workflow efficiency in TMJ diagnostics.